Assessment of Middle Ear Anatomy Teaching Methodologies Using Microscopy versus Endoscopy: A Randomized Comparative Study. Issue 5 (14th November 2018) - Anschuetz, Lukas; Huwendiek, Sören; Stricker, Daniel; Yacoub, Abraam; Wimmer, Wilhelm; Caversaccio, Marco
Abstract : Teaching methodologies for the anatomy of the middle ear have not been investigated greatly due to the middle ear's highly complex structure and hidden location inside of the temporal bone. The aim of this randomized study was to quantitatively compare the suitability of using microscope‐ and endoscope‐based methods for teaching the anatomy of the middle ear. We hypothesize that the endoscopic approach will be more efficient compared to the microscopic approach. To answer the study questions, 33 sixth‐year medical students, residents and otorhinolaryngology specialists were randomized either into the endoscopy or the microscopy group. Their anatomical knowledge was assessed using a structured anatomical knowledge test before and after each session. Each participant received tutoring on a human cadaveric specimen using one of the two methods. They then performed a hands‐on dissection. After 2–4 weeks, the same educational curriculum was repeated using the other technique. The mean gains in anatomical knowledge for the specialists, residents, and medical students were +19.0%, +34.6%, and +23.4%, respectively. Multivariate analyses identified a statistically significant increase in performance for the endoscopic method compared to the microscopic technique ( P  < 0.001). For the recall of anatomical structures during dissection, the endoscopic method outperformed the microscopic technique independently of the randomization or the prior training level of the attendees ( P  < 0.001). In conclusion, the endoscopic approach to middle ear anatomy education is associated to an improved gain in knowledge as compared to the microscopic approach. The participants subjectively preferred the endoscope for educational purposes.